Effectiveness of Extrinsic Incentives for Promoting Rural Waste Sorting in Developing Countries: Evidence from China. (21st April 2022) - Zhao, Aidong; Zhang, Limin; Ma, Xianlei; Gao, Fugang; Zhu, Honggen
Abstract : Rural areas in many developing countries lack an effective waste management system, leading to poor environmental hygiene. As an initial but integral step toward sustainable waste management, fostering better household compliance with waste‐sorting regulation has become an important policy agenda. This paper devotes attention to evaluating the effectiveness of extrinsic incentives, more specifically, reward–penalty schemes, on promoting rural households' participation in waste sorting. By exploiting an original survey of 1, 058 rural households conducted in the Taihu Basin of China, we empirically find that (1) reward–penalty scheme considerably promotes rural households' engagement with waste sorting; (2) the more stringently the scheme is implemented, the higher the probabilities of more frequent sorting; and (3) point reward, which can be exchanged for vouchers used in local stores, is the most effective extrinsic incentive for promoting waste sorting. The findings provide insights for enhancing rural waste sorting in the developing world.